GRP-085 Identification of Relevant Drug Interactions in Neonatal Intensive Care Units. (12th March 2013) - Cransac, A; Semama, D; Lazzarotti, A; Hugueny, J; Sgro, C; Ferdynus, C; Gouyon, JB; Fagnoni, P
Abstract : Background: Among the different types of medication errors, drug interactions may have serious consequences in Neonatal Intensive Care Units (NICU). However, they can be easily detected with appropriate tools, particularly in the context of a computerised prescribing system with pharmaceutical analysis. Purpose: The objective of this study was to calculate a theoretical criticality index, using a method inspired by the Failure Modes, Effects and Criticality Analysis (FMECA) method for each drug interactions identified in NICU in order to prioritise them to pharmacists and physicians. Materials and Methods: The study was a retrospective review of prescriptions in a French NICU. The study included prescriptions for preterm infants with gestational age below 33 weeks and hospitalised between January 2006 and December 2009. For each prescription, drug interactions were evaluated with the French Theriaque ® medication database. The criticality index of each drug interaction was calculated by multiplying occurrence, severity and detection scores. The scales of each score had been built by a multidisciplinary group. Severity and detection scores were assessed by pharmacists and physicians. Intraclass Correlation Coefficients (ICCs) were used to compare pharmacists' and physicians' scores, and a synthesis was realised. Results: Among the 907 prescriptions with at least 2 prescribed drugs (4605 prescriptions written, with 109 different drugs), 47 different drug interactions were identified with Theriaque ® . The 10 most critical drug interactions for pharmacists and physicians were detailed, and then a common medical and pharmaceutical synthesis was established. The ICC of detection was 0.75 (95% CI: 0.63–0.88), and the severity was 0.32 (95% CI: 0.08–0.56). Conclusions: This work highlights the importance of multidisciplinary collaboration in safe medication practise. This method can be used as a basis for future cooperation between medical teams and the pharmaceutical teams that make interventions. It is easily transferable to other medical specialties with the same objectives. No conflict of interest.